El huerto escolar como escenario práctico de enseñanza-aprendizaje de las Ciencias Naturales con los estudiantes de básica superior de la Unidad Educativa Nuestro Mundo Eco-Rio, año lectivo 2024-2025. - Paullán Sanunga, Cristian Alfredo (2025)
In the teaching-learning process of Natural Sciences, it is important to link theory with practice, however, in many educational institutions this does not happen. In the Nuestro Mundo Eco-Rio Educational Unit in the city of Riobamba, there are very few spaces for practical activities in the learning of this subject. For this reason, we propose the implementation of a school garden to promote the learning of Natural Sciences in upper elementary schools. We worked with 61 students in the eighth, ninth and tenth years of general basic education. The research design was non-experimental, field, cross-sectional and descriptive. For data collection, a structured survey was applied to the population considered, using a Likert scale questionnaire as an instrument. Upon analyzing the results of the research, it was determined that a high percentage of students consider the implementation of school gardens positive as a practical and interactive space to develop field activities that reinforce theoretical knowledge of the subject. As a conclusion, it was determined that the school garden awakened a greater interest in learning the subject, developing competencies in areas such as environmental care, scientific skills and healthy eating. Therefore, the implementation of school gardens is proposed as a practical scenario for active and participatory learning